2015
DOI: 10.1051/radiopro/2014023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiation risk to pediatric patients undergoing conventional X-ray examinations

Abstract: -Increasing concern has been expressed in the literature that the knowledge of physicians regarding the radiation risk values incurred during different radiological examinations is inadequate. This study determined the amount of organ doses and the radiation risks involved in pediatric radiology in terms of the age and sex of patients. The X-ray examinations of the chest, abdomen, pelvis and skull in patients of six age groups (newborn, 1-, 5-, 10-and 15-year-old, and adult) were investigated. Exposure data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
5
8
1
Order By: Relevance
“…There was no statistically significant differences in kVp, mAs, height, weight, and field size [26,27,29,35,37,38], but the field size in this study was significantly higher compared to other studies, which may have accounted for the unusual high dose observed in the 4 age groups [26,29,35].…”
Section: Discussioncontrasting
confidence: 80%
“…There was no statistically significant differences in kVp, mAs, height, weight, and field size [26,27,29,35,37,38], but the field size in this study was significantly higher compared to other studies, which may have accounted for the unusual high dose observed in the 4 age groups [26,29,35].…”
Section: Discussioncontrasting
confidence: 80%
“…Another difference between the REID values in our study and the other studies can be due to the fact that in the other studies, for obtaining cancer risk, the effective dose was simply multiplied by constant coef icients, while in our study, risk assessment was done based on the models published by the BEIR VII (14) . In general, the REID values for dental radiographies are about 10 times smaller than ones of conventional radiographies (29,30) .…”
Section: Discussionmentioning
confidence: 92%
“…Similar findings have been reported elsewhere in the literature. 9,21 Gonad protection is significant in pelvic radiography; the germ cells within the gonads are susceptible to radiation damage such as genetic and somatic malignancies. 6 Irradiating the lower part of the colon and pelvis bone is an added concern in paediatric pelvic radiography.…”
Section: Discussionmentioning
confidence: 99%